Solipsism: Understanding Japanese Culture Through the Novel "Namaku Hiroko" by N.H. DINI (A Critical Students Discussion Perspective) - Tetet Sulastri; Lukman Hakim (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
The aim of this research is to reveal the concept of solipsism in understanding Japanese culture in the novel Namaku Hiroko by N.H. Dini. This research raises three main problems, namely; Japanese culture, the author's perspective, and the manifestation of solipsism in literary works. The aim of this research was formulated to find out; 1) the author's perspective on solipsism in Japanese culture, and 2) the form of solipsism itself in literary works. Of course the literary work referred to here is the novel Namaku Hiroko by N.H. Dini. The theory of solipsism is used to understand the experience of the novel writer Namaku Hiroko in understanding culture, including the concepts and perspectives of Japanese culture as depicted in the work of N.H. Dini. Qualitative research methods with a phenomenological approach are used in this research to describe everything related to Japanese culture based on a critical student discussion. This study found that the principle of solipsism exists in Japanese culture as outlined by NH. Dini in Namaku Hiroko.